2021
DOI: 10.37291/2717638x.202123118
|View full text |Cite
|
Sign up to set email alerts
|

Science starts early: A literature review examining the influence of early childhood teachers’ perceptions of gender on teaching practices

Abstract: Women are underrepresented in science fields as compared to men and although much research has been dedicated to understanding this disparity, most has been conducted on older aged children. However, this excludes the youngest and arguably most impressionable group of students: preschoolers. This study reviewed the literature to investigate how early childhood teachers’ perceptions of gender influence their teaching practices. Qualitative analysis and coding of 31 articles resulted in five main categories: Tea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 65 publications
0
2
0
Order By: Relevance
“…For example, a study found that preschool girls' early interest in science is a predictor of future science achievement (Leibham et al, 2013). Recognising preschool children's early interest in science by teachers and planning activities around children's interests and learning needs are also important for future science achievement (Hamel, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…For example, a study found that preschool girls' early interest in science is a predictor of future science achievement (Leibham et al, 2013). Recognising preschool children's early interest in science by teachers and planning activities around children's interests and learning needs are also important for future science achievement (Hamel, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…• how play-based inquiry activities support children's conceptual understanding of thermal-_____________ insulation and engagement with scientific and engineering practices (Fragkiadaki et al, 2021;Miller & Saenz, 2021) • the role of language, question-explanation exchanges, and Dual Language Learning environment in learning science concepts (Åkerblom & Thorshag, 2021;Haber et al, 2021;Rumper et al, 2021) • how early childhood teachers' perceptions of gender influence their science teaching practices (Hamel, 2021).…”
mentioning
confidence: 99%